Migraine in antiphospholipid syndrome and hereditary thrombophilia: pregnancy-related clinical and diagnostic features and therapeutic issues - O. N. Voskresenskaya; L. R. Dashdamirova; J. Kh. Khizroeva; A. D. Makatsariya; V. O. Bitsadze (IRBIS LLC, 2020)
Introduction. Migraine is one of the most common primary headaches and a risk factor for cardiovascular and cerebrovascular diseases. Antiphospholipid syndrome (APS) and hereditary thrombophilia (HT) causing pathological pregnancy are highly associated with migraine. Timely migraine recognition related to APS and HT facilitates earlier initiation of thrombophilia pathogenetic therapy and prevention of potential complications.Aim: to analyze the literature data on migraine clinical and diagnostic features in APS and HT as well as pregnancy-related therapeutic issues.Materials and Methods. A search for scientific literature was conducted in electronic databases including PubMed, Google Scholar, eLibrary from 2004 until May 2024. The search methodological basis included the presence of the following keywords and their combinations in Russian and English: "migraine", "antiphospholipid syndrome", "thrombophilia", "migraine and pregnancy", "migraine and thrombophilia", "migraine and cardiovascular diseases". As a result, a total of 184 publications were identified. Next, 62 articles were included in the review.Results. At the current stage, neurologists have no means to diagnose migraine in APS and HT based on headache-intrinsic characteristics. Pregnancy increases a risk of thrombotic complications. A migraine observed in patient's history should be crucial while assessing pregnancy-related obstetric risk. While diagnosing migraine, neurologists need to examine patient obstetric history. The data on most effective and safe therapy for pregnancy-related migraine attacks remain scarce.Conclusion. The frequent association between APS and HT with migraine, the lack of clear migraine clinical features in thrombophilia, patients' reproductive age, and the high risk of thrombotic complications necessitate collaboration between neurologists and obstetricians-gynecologists for timely diagnostics and management of such patients. The impact of various types of antithrombotic therapy on migraine course requires further clarification. It is promising to conduct studies able to determine of whether migraine attack prevention can avoid adverse pregnancy outcomes in women with former migraine.